Routledge handbook of the informal economy - Elgin, Ceyhun (London Routledge, 2025)
Delve into the intricate landscape of the informal economy with the Routledge Handbook of Informal Economy, a groundbreaking volume that transcends conventional economic analysis by contextualizing it within a broader regulatory and social framework. This comprehensive handbook offers cutting-edge categorical, thematic, and regional analyses of the informal, or shadow, economy. An esteemed international ensemble of contributors draws on diverse economic perspectives, exploring a spectrum of definitions and measures, including household, firm-level, and employment-based metrics, alongside perceptional and model-based estimates. Employing a variety of econometric and methodological approaches, the volume provides both regional and global estimates of the informal economy's extent.
Keywords: Syndicalisation; Labor unions organizing; Business and economics